Pre-dispersion-free carbon nanotube composite powder, preparation method and application thereof
Patent Information
- Application Number
- CN202311533611.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-16
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-16
AI Technical Summary
该方案存在以下缺点:1、目前碳纳米管粉体分散难度高,客户无法直接使用;2、预分散液中,碳纳米管含量低(一般≤10%),85%以上的成分为溶剂,运输难度高、成本高
[0027]The above-mentioned method for preparing pre-dispersible carbon nanotube composite powder involves pre-mixing carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer with a solvent to form a carbon nanotube composite suspension. The resulting pre-dispersible carbon nanotube composite powder undergoes dispersion, foaming, and freeze-drying processes. This process yields a pre-dispersible carbon nanotube composite powder with good dispersibility, allowing for direct use and relatively easy dispersion during application. Because the carbon nanotube composite powder is prepared directly, solvent is eliminated during transportation, significantly reducing transportation costs. The carbon nanotube composite powder provided by this invention eliminates the need for large amounts of solvent, greatly reducing transportation costs and improving transportation efficiency. Furthermore, the carbon nanotube composite powder provided by this invention is easily dispersed, eliminating the need for customers to use high-shear equipment for dispersion. Being solvent-free, the carbon nanotube composite powder provided by this invention is unaffected by the customer's solvent system and can be used in products with different solvent systems.
Smart Images

Figure CN117566728B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of materials technology, and in particular to a carbon nanotube composite powder that does not require pre-dispersion, its preparation method, and its application. Background Technology
[0002] Carbon nanotubes have a wide range of applications due to their unique structure and excellent properties. They hold immense potential in various products and materials, including conductive agents for lithium batteries, conductive plastics, transparent conductive films, supercapacitors, conductive inks, and high-strength "superfibers." For example, carbon nanotubes are 100 times stronger than steel of the same volume, yet weigh only 1 / 6 to 1 / 7 of steel, making them suitable for use as high-strength materials. Simultaneously, the electrical properties of carbon nanotubes also give them broad application prospects in the field of electronic devices.
[0003] However, while carbon nanotubes have good electrical conductivity, they are difficult to disperse and cannot be used directly. Currently, the main method is to pre-disperse carbon nanotube powder in a solvent using dispersion equipment to prepare a carbon nanotube pre-dispersion liquid before delivery to customers. This approach has the following drawbacks: 1. Currently, the dispersion of carbon nanotube powder is difficult, making it unsuitable for direct use by customers; 2. The carbon nanotube content in the pre-dispersion liquid is low (generally ≤10%), with over 85% being solvent, resulting in high transportation difficulty and cost. Summary of the Invention
[0004] Therefore, it is necessary to provide a carbon nanotube composite powder that is relatively easy to disperse and can reduce transportation costs without pre-dispersion, as well as its preparation method and applications.
[0005] In a first aspect, this application provides a method for preparing carbon nanotube composite powder without pre-dispersion, comprising the following steps:
[0006] Carbon nanotube powder, carbon black powder, dispersant, foaming and stabilizing agent and solvent are mixed and stirred to form a carbon nanotube composite suspension;
[0007] The nanotube composite suspension is dispersed.
[0008] The nanotube composite suspension is subjected to foam generation treatment to form a composite foam liquid;
[0009] The composite foam liquid was freeze-dried to obtain the carbon nanotube composite powder.
[0010] In one embodiment, the mass ratio of the carbon nanotube powder, carbon black powder, dispersant and foam stabilizer is (3-10):(0-3):(0.5-5):(0.2-3).
[0011] In one embodiment, the carbon nanotube composite suspension comprises, by mass percentage, the following components in the following mass percentages: 3%-10% carbon nanotube powder, 0%-3% carbon black powder, 0.5%-5% dispersant, 0.2%-3% foaming and stabilizing agent, and the balance being solvent.
[0012] In one embodiment, the mass ratio of the carbon nanotube powder, carbon black powder, dispersant and foam stabilizer is (3-10):(0.1-3):(0.5-5):(0.2-3).
[0013] In one embodiment, the carbon nanotube composite suspension comprises, by mass percentage, the following components in the following mass percentages: 3%-10% carbon nanotube powder, 0.1%-3% carbon black powder, 0.5%-5% dispersant, 0.2%-3% foaming and stabilizing agent, and the balance being solvent.
[0014] In other words, the carbon nanotube composite powder without pre-dispersion of this application may contain carbon black powder, that is, in the case of a mass ratio of 0.1-3 or a mass percentage of 0.1%-3%, or may not contain carbon black powder, that is, in the case of a mass ratio of 0 or a mass percentage of 0%.
[0015] In one embodiment, the carbon nanotube powder has a nanotube diameter of 8-50 nm, preferably 20-30 nm, and a specific surface area of 60-300 m² / g, preferably 120-240 m² / g.
[0016] In one embodiment, the carbon black has a specific surface area of 50-130 m² / g, preferably 50-80 m² / g; and an oil absorption value of 80-360 mL / 100g, preferably 80-260 mL / 100g.
[0017] In one embodiment, the dispersant includes at least one of polyvinylpyrrolidone and sodium dodecylbenzenesulfonate;
[0018] In one embodiment, the foaming stabilizer is at least one of sodium lauryl ether sulfate, sodium lauryl sulfate, and polyvinyl alcohol;
[0019] In one embodiment, the solvent is water, preferably deionized water.
[0020] In one embodiment, a high-shear device is used to disperse the nanotube composite suspension.
[0021] In one embodiment, a foam generator is used to treat the nanotube composite suspension to generate foam, forming a composite foam liquid.
[0022] In one embodiment, the foam suspension is subjected to two-stage refrigeration before freeze-drying, wherein the first stage refrigeration temperature is 2-10°C and the second stage refrigeration temperature is -60°C to -10°C.
[0023] In one embodiment, the carbon nanotube composite suspension does not contain carbon black powder. In other words, the technical solution of this application may not contain carbon black, or the carbon nanotube composite suspension may not contain carbon black powder. Alternatively, this application also provides a method for preparing a pre-dispersible carbon nanotube composite powder, comprising the following steps: mixing and stirring carbon nanotube powder, a dispersant, a foaming and stabilizing agent, and a solvent to form a carbon nanotube composite suspension; dispersing the nanotube composite suspension; foaming the nanotube composite suspension to form a composite foam liquid; and freeze-drying the composite foam liquid to obtain the carbon nanotube composite powder. That is to say, in this embodiment, except for the absence of carbon black powder, the preparation method is the same as the pre-dispersible carbon nanotube composite powder preparation method provided in the first aspect.
[0024] Secondly, this application provides a carbon nanotube composite powder that does not require pre-dispersion, prepared using the preparation method described in any of the above embodiments.
[0025] Thirdly, this application provides a pre-dispersion-free carbon nanotube composite powder, comprising the following components: carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer, wherein the mass ratio of the carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer is (3-10):(0-3):(0.5-5):(0.2-3). Alternatively, the mass ratio of the carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer may be (3-10):(0.1-3):(0.5-5):(0.2-3).
[0026] Fourthly, this application provides an application of the carbon nanotube composite powder as described in any of the above embodiments in lithium battery conductive agents, conductive plastics, transparent conductive films, supercapacitors, conductive inks, and high-strength superfibers.
[0027] The above-mentioned method for preparing pre-dispersible carbon nanotube composite powder involves pre-mixing carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer with a solvent to form a carbon nanotube composite suspension. The resulting pre-dispersible carbon nanotube composite powder undergoes dispersion, foaming, and freeze-drying processes. This process yields a pre-dispersible carbon nanotube composite powder with good dispersibility, allowing for direct use and relatively easy dispersion during application. Because the carbon nanotube composite powder is prepared directly, solvent is eliminated during transportation, significantly reducing transportation costs. The carbon nanotube composite powder provided by this invention eliminates the need for large amounts of solvent, greatly reducing transportation costs and improving transportation efficiency. Furthermore, the carbon nanotube composite powder provided by this invention is easily dispersed, eliminating the need for customers to use high-shear equipment for dispersion. Being solvent-free, the carbon nanotube composite powder provided by this invention is unaffected by the customer's solvent system and can be used in products with different solvent systems.
[0028] The principle of the pre-dispersion-free carbon nanotube composite powder of this application is as follows: a foaming and stabilizing agent is introduced, and a carbon nanotube composite foam liquid is prepared by a foam generator. The foam liquid is then freeze-dried to obtain a porous solid. By introducing foam, the agglomeration of carbon nanotubes during the drying process is reduced, thereby maintaining the carbon nanotube composite powder in a well-dispersed state. This brings the following advantages: compared with conventional carbon nanotube powders, the carbon nanotube composite powder provided by this invention is easy to disperse and can be uniformly distributed in the customer's product system without strong dispersion conditions, giving full play to the performance advantages of carbon nanotubes; compared with commercially available carbon nanotube slurries, the carbon nanotube composite powder provided by this invention is solvent-free, convenient to transport, low in cost, and widely applicable. Attached Figure Description
[0029] Figure 1 This is a step diagram illustrating a method for preparing carbon nanotube composite powder without pre-dispersion, according to one embodiment. Detailed Implementation
[0030] To facilitate understanding of this application and to make the aforementioned objectives, features, and advantages of this application more apparent, a detailed description of specific embodiments of this application is provided below in conjunction with the accompanying drawings. Numerous specific details are set forth in the following description to provide a thorough understanding of this application, and preferred embodiments are shown in the accompanying drawings. However, this application can be implemented in many different forms and is not limited to the embodiments described herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the disclosure of this application. This application can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application; therefore, this application is not limited to the specific embodiments disclosed below. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0031] In one aspect, this application provides a method for preparing carbon nanotube composite powder without pre-dispersion. Please refer to [link to relevant documentation]. Figure 1 The preparation method includes the following steps:
[0032] S110: Carbon nanotube powder, carbon black powder, dispersant, foaming stabilizer and solvent are mixed and stirred to form a carbon nanotube composite suspension;
[0033] In this embodiment, a carbon nanotube composite suspension is formed by pre-mixing and stirring carbon nanotube powder, carbon black powder, dispersant, foaming and stabilizing agent, and solvent. Preferably, the solvent is water, and more preferably, deionized water. Of course, solvents other than water can also be used.
[0034] Specifically, a carbon nanotube composite suspension is formed by mechanical stirring. Specifically, a mechanical stirrer is used to stir the carbon nanotube powder, carbon black powder, dispersant, foaming stabilizer and solvent.
[0035] In one embodiment, the mass ratio of the carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer is (3-10):(0.1-3):(0.5-5):(0.2-3). Thus, the carbon nanotube composite powder prepared using the following mass ratio exhibits good distribution and achieves a good dispersion-free effect.
[0036] In one embodiment, the carbon nanotube composite suspension comprises, by mass percentage, the following components in the following mass percentages: 3%-10% carbon nanotube powder, 0.1%-3% carbon black powder, 0.5%-5% dispersant, 0.2%-3% foaming and stabilizing agent, and the balance being solvent.
[0037] In one embodiment, a mechanical mixer is used to mix the components at a stirring speed of 2-15 m / s and a stirring time of 10-180 min. The applicant's research has shown that using the above stirring speed and time, combined with the carbon nanotube composite suspension comprising the following components by mass percentage: 3%-10% carbon nanotube powder, 0.1%-3% carbon black powder, 0.5%-5% dispersant, 0.2%-3% foaming and stabilizing agent, and the balance solvent, results in better subsequent dispersion of the carbon nanotube powder.
[0038] In one embodiment, the carbon nanotube powder has a nanotube diameter of 8-50 nm, preferably 20-30 nm; and a specific surface area of 60-300 m² / g, preferably 120-240 m² / g. The applicant has found that using carbon nanotube powder with the above-mentioned diameter and specific surface area, especially when combined with 3%-10% carbon nanotube powder in a carbon nanotube composite suspension, can result in better dispersion of carbon nanotubes. Furthermore, the carbon nanotube composite powder prepared by foaming and freeze-drying processes has a better dispersion effect.
[0039] In one embodiment, the carbon black has a specific surface area of 50-130 m² / g, preferably 50-80 m² / g; and an oil absorption value of 80-360 mL / 100g, preferably 80-260 mL / 100g. Thus, using carbon black with a specific surface area and oil absorption value, especially with 0.1%-3% of combined carbon black powder, results in good carbon black dispersion, and the carbon nanotube composite powder prepared by foaming and freeze-drying processes exhibits good dispersion.
[0040] In one embodiment, the dispersant includes at least one of polyvinylpyrrolidone and sodium dodecylbenzenesulfonate; for example, the foaming and stabilizing agent is at least one of sodium lauryl ether sulfate, sodium lauryl sulfate, and polyvinyl alcohol. Thus, by introducing the foaming and stabilizing agent, a carbon nanotube composite foam liquid is prepared using a foam generator, and then the foam liquid is freeze-dried to obtain a porous solid. By introducing foam, the agglomeration of carbon nanotubes during the drying process is reduced, thereby maintaining the carbon nanotube composite powder in a well-dispersed state. Using the above-mentioned foaming and stabilizing agent and dispersant, especially using 0.5%-5% dispersant and 0.2%-3% foaming and stabilizing agent, ensures excellent subsequent dispersion and foaming effects, thereby ensuring the successful preparation of carbon nanotube composite powder.
[0041] In one embodiment, the solvent is water, preferably deionized water.
[0042] S120: Dispersion treatment is performed on the nanotube composite suspension;
[0043] In this embodiment, the nanotube composite suspension is dispersed to ensure that each component is well dispersed in the solvent, which facilitates subsequent foam generation.
[0044] In one embodiment, a high-shear device is used to disperse the nanotube composite suspension, thereby achieving better dispersion. In one embodiment, the high-shear device is either a sand mill or a homogenizer. Specifically, the shear dispersion conditions are suitable dispersion processes for the high-shear dispersion device.
[0045] In one specific embodiment, when a sand mill is used for dispersion, the grinding media is zirconium beads with a diameter of 0.1-2.0 mm, preferably 0.6-1.2 mm; the dispersion linear velocity is 6 m / s-15 m / s, preferably 8-13 m / s; and the ball-to-particle ratio is 60:1 to 150:1, preferably 80:1 to 120:1. In this way, the sand mill can effectively disperse the nanotube composite suspension, ensuring the dispersion effect, which facilitates subsequent foam generation and freeze-drying to form carbon nanotube composite powder with good dispersion effect.
[0046] In one specific embodiment, when a homogenizer is used for dispersion, the dispersion pressure is 30-150 MPa, preferably 50-100 MPa; in this way, the homogenizer can effectively disperse the nanotube composite suspension, ensuring the dispersion effect, which facilitates subsequent foam generation and freeze-drying to form carbon nanotube composite powder with good dispersion effect.
[0047] In one specific embodiment, the composite suspension is dispersed to a viscosity ≤1000 mPa·s (measured using a rotational viscometer with rotor No. 3 at 30 rpm) using a high-shear device, preferably ≤500 mPa·s; and a particle size D90 ≤5 μm, preferably D90 ≤1 μm. In this way, the dispersion treatment of the nanotube composite suspension to achieve the above-mentioned viscosity and particle size can ensure that carbon nanotube composite powder with good dispersion effect is formed after subsequent foaming and freeze-drying.
[0048] S130: The nanotube composite suspension is subjected to foam generation treatment to form a composite foam liquid;
[0049] In this embodiment, the introduction of foam reduces the agglomeration of carbon nanotubes during the drying process, thereby maintaining the carbon nanotube composite powder in a well-dispersed state. This brings the following advantages: compared with conventional carbon nanotube powder, the carbon nanotube composite powder provided by this invention is easy to disperse and can be uniformly distributed in the customer's product system without strong dispersion conditions, thus leveraging the performance advantages of carbon nanotubes; compared with commercially available carbon nanotube slurries, the carbon nanotube composite powder provided by this invention is solvent-free, convenient to transport, low in cost, and widely applicable.
[0050] In one embodiment, a foam generator is used to treat the nanotube composite suspension to generate foam, forming a composite foam liquid. This effectively treats the nanotube composite suspension to generate foam. Specifically, the foam generator can be any appliance capable of producing foam, including but not limited to positive pressure mechanical stirring equipment, positive pressure oscillation equipment, foam pumps, etc.
[0051] In one embodiment, the apparent density of the composite foam liquid is 0.01 g / mL to 0.25 g / mL. Thus, the applicant has found that using a composite foam liquid with the above apparent density allows for better subsequent freeze-drying, and after freeze-drying, it can form a powder with good dispersion.
[0052] In one embodiment, the bubble diameter of the composite foam liquid is 0.1–2 mm, preferably 0.1–0.8 mm, and more preferably 0.1–0.5 mm. Thus, using a composite foam liquid with such a bubble diameter facilitates subsequent freeze-drying to form powder and provides good dispersion.
[0053] S140: Freeze-dry the composite foam liquid to obtain the carbon nanotube composite powder.
[0054] In this embodiment, the carbon nanotube composite powder without pre-dispersion is obtained by freeze-drying the composite foam liquid.
[0055] In one embodiment, the foam suspension is subjected to two-stage refrigeration before freeze-drying, wherein the first stage refrigeration temperature is 2-10°C and the second stage refrigeration temperature is -60°C to -10°C.
[0056] In one specific implementation, the first refrigerated section is placed in the first refrigeration equipment A for the first refrigeration, and the refrigeration temperature is 0-4℃. In the refrigeration equipment A, the temperature of the foam suspension is reduced to 2-10℃, preferably 2-6℃.
[0057] The second stage of refrigeration involves placing the composite foam liquid in the second refrigeration equipment B at a refrigeration temperature of -60℃ to -10℃, where it is rapidly frozen until solidified to obtain a porous condensate.
[0058] Thus, by employing the above two-stage refrigeration, porous condensates can be obtained more effectively, thereby ensuring that the carbon nanotube composite powder obtained after freeze-drying is pre-dispersible.
[0059] In one embodiment, during freeze-drying, the freeze-drying cold trap temperature is -30 to -60°C, preferably -45 to -60°C. The vacuum degree is 0.02 MPa to 0.1 MPa, which allows for better freeze-drying. During freeze-drying, the frozen composite foam liquid, i.e., the porous condensate, is dried into the carbon nanotube composite powder without pre-dispersion by gradually increasing the temperature.
[0060] The above-mentioned method for preparing pre-dispersible carbon nanotube composite powder involves pre-mixing carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer with a solvent to form a carbon nanotube composite suspension. The resulting pre-dispersible carbon nanotube composite powder undergoes dispersion, foaming, and freeze-drying processes. This process yields a pre-dispersible carbon nanotube composite powder with good dispersibility, allowing for direct use and relatively easy dispersion during application. Because the carbon nanotube composite powder is prepared directly, solvent is eliminated during transportation, significantly reducing transportation costs. The carbon nanotube composite powder provided by this invention eliminates the need for large amounts of solvent, greatly reducing transportation costs and improving transportation efficiency. Furthermore, the carbon nanotube composite powder provided by this invention is easily dispersed, eliminating the need for customers to use high-shear equipment for dispersion. Being solvent-free, the carbon nanotube composite powder provided by this invention is unaffected by the customer's solvent system and can be used in products with different solvent systems.
[0061] The principle of the pre-dispersion-free carbon nanotube composite powder of this application is as follows: a foaming and stabilizing agent is introduced, and a carbon nanotube composite foam liquid is prepared by a foam generator. The foam liquid is then freeze-dried to obtain a porous solid. By introducing foam, the agglomeration of carbon nanotubes during the drying process is reduced, thereby maintaining the carbon nanotube composite powder in a well-dispersed state. This brings the following advantages: compared with conventional carbon nanotube powders, the carbon nanotube composite powder provided by this invention is easy to disperse and can be uniformly distributed in the customer's product system without strong dispersion conditions, giving full play to the performance advantages of carbon nanotubes; compared with commercially available carbon nanotube slurries, the carbon nanotube composite powder provided by this invention is solvent-free, convenient to transport, low in cost, and widely applicable.
[0062] Secondly, this application provides a carbon nanotube composite powder that does not require pre-dispersion, prepared using the preparation method described in any of the above embodiments.
[0063] The aforementioned carbon nanotube composite powder, which requires no pre-dispersion, is prepared using the preparation method described in any of the preceding embodiments. By introducing foam, the agglomeration of carbon nanotubes during the drying process is reduced, thereby maintaining the carbon nanotube composite powder in a well-dispersed state. This brings the following advantages: Compared with conventional carbon nanotube powders, the carbon nanotube composite powder provided by this invention is easy to disperse and can be uniformly distributed in the customer's product system without strong dispersion conditions, thus leveraging the performance advantages of carbon nanotubes; compared with commercially available carbon nanotube slurries, the carbon nanotube composite powder provided by this invention is solvent-free, convenient to transport, low in cost, and widely applicable.
[0064] Thirdly, this application provides a pre-dispersible carbon nanotube composite powder, comprising the following components: carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer, wherein the mass ratio of the carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer is (3-10):(0-3):(0.5-5):(0.2-3), or, for example, the mass ratio of the carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer is (3-10):(0.1-3):(0.5-5):(0.2-3). In a specific embodiment, the components are prepared by adding solvent, mixing and stirring, dispersing, foam generation, and freeze-drying. In a specific embodiment, the components are fully mixed to form the pre-dispersible carbon nanotube composite powder.
[0065] Fourthly, this application provides an application of the carbon nanotube composite powder described in any of the above embodiments in lithium battery conductive agents, conductive plastics, transparent conductive films, supercapacitors, conductive inks, and high-strength superfibers. Of course, the carbon nanotube composite powder prepared in this application is not limited to the above-mentioned fields.
[0066] Additionally, it should be noted that the carbon nanotube composite powder and its preparation method in this application may also not contain carbon black powder.
[0067] The present application will be further described below with reference to specific embodiments.
[0068] Example 1:
[0069] The method for preparing the pre-dispersion-free carbon nanotube composite powder in this embodiment includes the following steps:
[0070] 1. Prepare 1 kg of carbon nanotube composite suspension.
[0071] a) Weigh out 30g of carbon nanotube powder, 20g of carbon black powder, 25g of dispersant, 8g of foaming and stabilizing agent, and 917g of deionized water.
[0072] b) Mix using a mechanical mixer for 30 minutes at a linear speed of 5 m / s;
[0073] c) The average diameter of the carbon nanotubes is approximately 25 nm, and the specific surface area is 144 m² / g.
[0074] d) The carbon black has a specific surface area of 65 m² / g and an oil absorption value of 171 g / 100 mL.
[0075] e) The dispersant is polyvinylpyrrolidone.
[0076] f) The foaming and stabilizing agent is sodium lauryl ether sulfate.
[0077] 2. Disperse the above composite suspension using a sand mill with a sand mill chamber volume of 0.5L.
[0078] a) The grinding media is zirconium beads with a diameter of 0.8 mm, a dispersion linear velocity of 12 m / s, and a ball-to-material ratio of 90:1.
[0079] b) The composite suspension was dispersed to a viscosity ≤ 500 mPa·s, the measured viscosity was 120 mPa·s, and the measured particle size was D90 = 0.676 μm.
[0080] 3. Foam is generated in the composite suspension by a foam pump, and the foam slurry is transported to transfer container A to obtain composite foam liquid;
[0081] a) The apparent density of the composite foam liquid is 0.0152 g / mL.
[0082] 4. Take the foam suspension of the composite foam liquid and put it into the refrigeration equipment for two-stage refrigeration.
[0083] a) The two-stage refrigeration, the first stage refrigeration equipment A, the refrigeration temperature is set to 0℃, in refrigeration equipment A, the temperature of the foam suspension is reduced to 2-10℃, the actual measured temperature is 3.5℃.
[0084] b) The second stage of refrigeration, the second stage refrigeration equipment B, the refrigeration temperature is -45℃, the composite foam liquid is placed in the refrigeration equipment and quickly frozen until solidified to obtain a porous solidified solid.
[0085] 5. Place the porous solidified material in a freeze dryer for freeze drying. The freeze dryer's cold trap temperature is -60℃, and the vacuum degree is maintained at 0.05MPa. After the porous solidified material is completely dried, carbon nanotube composite powder without pre-dispersion is obtained.
[0086] Comparative Example 1: The first sample in the comparative example is the carbon nanotube powder used in step 1 of Example 1.
[0087] Comparative Example 2: The sample in Comparative Example 2 is the carbon black powder used in step 1 of Example 1.
[0088] Comparative Example 3: The composite powder formed by mixing carbon nanotubes and carbon black in a 3:2 ratio as in Example 1.
[0089] Comparative Example 4:
[0090] Comparative Example 4 is the pre-dispersion obtained in Example 1, as detailed below.
[0091] 1. Prepare 1 kg of carbon nanotube composite suspension.
[0092] a) Weigh out 30g of carbon nanotube powder, 20g of carbon black powder, 25g of dispersant, 8g of foaming and stabilizing agent, and 917g of deionized water.
[0093] b) Mix using a mechanical mixer for 30 minutes at a linear speed of 5 m / s.
[0094] c) The average diameter of the carbon nanotubes is approximately 25 nm, and the specific surface area is 144 m² / g.
[0095] d) The carbon black has a specific surface area of 65 m² / g and an oil absorption value of 171 g / 100 mL.
[0096] e) The dispersant is polyvinylpyrrolidone.
[0097] f) The foaming and stabilizing agent is sodium lauryl ether sulfate.
[0098] 2. The above composite suspension is dispersed using a sand mill with a sand mill chamber volume of 0.5L to obtain a pre-dispersed liquid.
[0099] a) The grinding media is zirconium beads with a diameter of 0.8 mm, a dispersion linear velocity of 12 m / s, and a ball-to-material ratio of 90:1.
[0100] b) The composite suspension was dispersed to a viscosity ≤ 500 mPa·s, the measured viscosity was 120 mPa·s, and the measured particle size was D90 = 0.676 μm.
[0101] Comparative Example 5:
[0102] To obtain a pre-dispersion solution for Comparative Example 4, the process of direct freezing followed by lyophilization without foaming was described below:
[0103] 1. Prepare 1 kg of carbon nanotube composite suspension.
[0104] a) Weigh out 30g of carbon nanotube powder, 20g of carbon black powder, 25g of dispersant, 8g of foaming and stabilizing agent, and 917g of deionized water.
[0105] b) Mix using a mechanical mixer for 30 minutes at a linear speed of 5 m / s.
[0106] c) The average diameter of the carbon nanotubes is approximately 25 nm, and the specific surface area is 144 m² / g.
[0107] d) The carbon black has a specific surface area of 65 m² / g and an oil absorption value of 171 g / 100 mL.
[0108] e) The dispersant is polyvinylpyrrolidone.
[0109] f) The foaming and stabilizing agent is sodium lauryl ether sulfate.
[0110] 2. The above composite suspension is dispersed using a sand mill with a sand mill chamber volume of 0.5L to obtain a pre-dispersed liquid.
[0111] a) The grinding media is zirconium beads with a diameter of 0.8 mm, a dispersion linear velocity of 12 m / s, and a ball-to-material ratio of 90:1.
[0112] b) The composite suspension was dispersed to a viscosity ≤ 500 mPa·s, the measured viscosity was 120 mPa·s, and the measured particle size was D90 = 0.676 μm.
[0113] 3. Place the pre-dispersed liquid into a refrigeration unit for secondary refrigeration.
[0114] a) The two-stage refrigeration, the first stage refrigeration equipment A, the refrigeration temperature is set to 0℃, in refrigeration equipment A, the temperature of the pre-dispersed liquid is reduced to 2-10℃.
[0115] b) The second-stage refrigeration, the second-stage refrigeration equipment B, the refrigeration temperature is -45℃, the composite foam liquid is placed in the refrigeration equipment and quickly frozen until solidified to obtain solidified solid.
[0116] 4. Place the solidified material in a freeze dryer for freeze drying. The freeze dryer's cold trap temperature is -60℃, and the vacuum degree is maintained at 0.05MPa. After the porous solidified material is completely dried, a comparative sample is obtained.
[0117] Comparative Example 6:
[0118] The pre-dispersion obtained in Comparative Example 4 was directly dried. Details are as follows:
[0119] 1. Prepare 1 kg of carbon nanotube composite suspension.
[0120] a) Weigh out 30g of carbon nanotube powder, 20g of carbon black powder, 25g of dispersant, 8g of foaming and stabilizing agent, and 917g of deionized water.
[0121] b) Mix using a mechanical mixer for 30 minutes at a linear speed of 5 m / s.
[0122] c) The average diameter of the carbon nanotubes is approximately 25 nm, and the specific surface area is 144 m² / g.
[0123] d) The carbon black has a specific surface area of 65 m² / g and an oil absorption value of 171 g / 100 mL.
[0124] e) The dispersant is polyvinylpyrrolidone.
[0125] f) The foaming and stabilizing agent is sodium lauryl ether sulfate.
[0126] 2. The above composite suspension is dispersed using a sand mill with a sand mill chamber volume of 0.5L to obtain a pre-dispersed liquid.
[0127] a) The grinding media is zirconium beads with a diameter of 0.8 mm, a dispersion linear velocity of 12 m / s, and a ball-to-material ratio of 90:1.
[0128] b) The composite suspension was dispersed to a viscosity ≤ 500 mPa·s, the measured viscosity was 120 mPa·s, and the measured particle size was D90 = 0.676 μm.
[0129] 3. Place the pre-dispersion liquid in a 120℃ forced-air drying oven to dry, and obtain the sample of Comparative Example Six.
[0130] The dispersibility and conductivity of the composite powder were characterized by testing the electrode resistivity, particle size D90, and secondary dispersion particle size D90.
[0131] The test methods for Example 1 and Comparative Examples 1-6 are as follows:
[0132] Electrode resistivity:
[0133] 1. Prepare the positive electrode slurry. Weigh each material into a beaker according to the following ratio: conductive agent (carbon nanotubes or carbon black, or a combination of both): PVDF (polyvinylidene fluoride): single-crystal nickel-cobalt-manganese ternary material (NCM523) = 0.7:1.5:97.8. Add the solvent N-methylpyrrolidone to make the total solid content 68% to 72%.
[0134] 2. Disperse the positive electrode slurry for 150 minutes at a linear velocity of 3 m / s using a mechanical mixer;
[0135] 3. Coating. The prepared positive electrode slurry is coated onto the insulating film using a 200μm doctor blade to obtain a wet electrode film;
[0136] 4. Drying. Place the wet electrode film in a 120℃ forced-air drying oven and bake for 15 minutes to obtain the dried electrode film;
[0137] 5. Cutting and Testing. Cut the dried electrode sheets into samples of a fixed size and test the resistivity of the samples using a four-probe resistivity meter.
[0138] Electrode resistivity can be used to evaluate the degree of dispersion of carbon nanotubes. The better the dispersion, the more complete the conductive network, and the lower the resistivity.
[0139] Particle size D90:
[0140] 1. Dilute the sample with deionized water to a solid content of 0.1%;
[0141] 2. Use a laser particle size analyzer to test the particle size distribution of the sample and read the D90 value;
[0142] 3. Particle size D90 can characterize the particle size of the sample.
[0143] Secondary dispersion particle size D90:
[0144] 1. Prepare a suspension with 3% carbon nanotube content using deionized water;
[0145] 2. Stir with a mechanical mixer for 30 minutes at a linear speed of 3 m / s to obtain a secondary pre-dispersion.
[0146] 3. Dilute the secondary predispersant with deionized water to a solid content of 0.1%;
[0147] 4. Use a laser particle size analyzer to test the particle size distribution of the sample and read the D90 value.
[0148] The secondary dispersion particle size D90 can characterize the degree of dispersion of a sample under simple dispersion conditions.
[0149] The above testing methods are only used as reference methods to demonstrate the effects and advantages of the present invention, and do not impose any limitations on the solutions provided by the present invention.
[0150] The experimental results are shown in Table 1.
[0151] Table 1. Experimental results of Example 1 and Comparative Examples 1 to 6
[0152]
[0153]
[0154] As can be seen from the table above, the carbon nanotube composite powder provided by the present invention (Example 1) is easier to disperse than conventional carbon nanotubes (Comparative Example 1). The carbon nanotube composite powder can be well dispersed under simple stirring conditions (mechanical stirring at a linear speed of 3 m / s). It has a small particle size and can significantly reduce the resistivity of the electrode when used in the positive electrode of lithium-ion batteries.
[0155] Compared to carbon black products (Comparative Example 2), carbon nanotube composite powder exhibits a significant advantage in electrical conductivity and has the same dispersibility as carbon black.
[0156] Compared to conventional composite powders made by simply mixing carbon nanotubes and carbon black (Comparative Example 3), carbon nanotube composite powders are easier to disperse and have better conductivity.
[0157] Compared to conventional carbon nanotube predispersants (Comparative Example 4), the conductivity and dispersibility of carbon nanotube composite powder are not significantly different from those of the predispersant, but it is solvent-free and more convenient and faster to transport.
[0158] Compared to conventional freeze-dried products (Comparative Example 5), the solution provided by this invention is easier to disperse and has better conductivity;
[0159] The conventionally dried sample (Comparative Example 6) could not be dispersed again at all.
[0160] The above-mentioned method for preparing pre-dispersible carbon nanotube composite powder involves pre-mixing carbon nanotube powder, carbon black powder, dispersant, and foaming stabilizer with a solvent to form a carbon nanotube composite suspension. The resulting pre-dispersible carbon nanotube composite powder undergoes dispersion, foaming, and freeze-drying processes. This process yields a pre-dispersible carbon nanotube composite powder with good dispersibility, allowing for direct use and relatively easy dispersion during application. Because the carbon nanotube composite powder is prepared directly, solvent is eliminated during transportation, significantly reducing transportation costs. The carbon nanotube composite powder provided by this invention eliminates the need for large amounts of solvent, greatly reducing transportation costs and improving transportation efficiency. Furthermore, the carbon nanotube composite powder provided by this invention is easily dispersed, eliminating the need for customers to use high-shear equipment for dispersion. Being solvent-free, the carbon nanotube composite powder provided by this invention is unaffected by the customer's solvent system and can be used in products with different solvent systems.
[0161] The principle of the pre-dispersion-free carbon nanotube composite powder of this application is as follows: a foaming and stabilizing agent is introduced, and a carbon nanotube composite foam liquid is prepared by a foam generator. The foam liquid is then freeze-dried to obtain a porous solid. By introducing foam, the agglomeration of carbon nanotubes during the drying process is reduced, thereby maintaining the carbon nanotube composite powder in a well-dispersed state. This brings the following advantages: compared with conventional carbon nanotube powders, the carbon nanotube composite powder provided by this invention is easy to disperse and can be uniformly distributed in the customer's product system without strong dispersion conditions, giving full play to the performance advantages of carbon nanotubes; compared with commercially available carbon nanotube slurries, the carbon nanotube composite powder provided by this invention is solvent-free, convenient to transport, low in cost, and widely applicable.
[0162] The technical features of the embodiments described above can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as the combination of these technical features does not contradict each other, it should be considered within the scope of this specification. It should be noted that the terms "in one embodiment," "for example," and "again," etc., in this application are intended to illustrate the application and not to limit it. The embodiments described above only illustrate several implementation methods of this application, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the patent application. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.
Claims
1. A method for preparing carbon nanotube composite powder without pre-dispersion, characterized in that, Includes the following steps: Carbon nanotube powder, carbon black powder, dispersant, foaming and stabilizing agent, and solvent are mixed and stirred to form a carbon nanotube composite suspension. The carbon nanotube composite suspension comprises the following components by mass percentage: 3% carbon nanotube powder, 2% carbon black powder, 2.5% dispersant, 0.8% foaming and stabilizing agent, and the balance being deionized water. The dispersant is polyvinylpyrrolidone, and the foaming and stabilizing agent is sodium lauryl ether sulfate. The carbon nanotube powder has a nanotube diameter of 25 nm and a specific surface area of 144 m². 2 / g, the specific surface area of the carbon black powder is 65m² 2 / g, oil absorption value is 171mL / 100g; The nanotube composite suspension was dispersed using a sand mill as a high-shear device, with zirconium beads as the grinding media. The grinding media diameter was 0.8 mm, the dispersion linear velocity was 12 m / s, the ball-to-particle ratio was 90:1, and the viscosity of the dispersed nanotube composite suspension was 120 mPa·s with a particle size D90 = 0.676 μm. The nanotube composite suspension is subjected to foam generation treatment to form a composite foam liquid; wherein a foam pump is used as a foam generator to form a composite foam liquid with an apparent density of 0.0152 g / mL and a bubble diameter of 0.1-0.5 mm. The composite foam liquid was freeze-dried to obtain the carbon nanotube composite powder. The composite foam liquid underwent two-stage refrigeration treatment before freeze-drying: the first stage refrigeration temperature was 0℃, and the measured temperature of the foam suspension after refrigeration was 3.5℃; the second stage refrigeration temperature was -45℃, freezing until the composite foam liquid solidified into a porous solid; the freeze-drying cold trap temperature was -60℃ and the vacuum degree was 0.05MPa, thus obtaining the carbon nanotube composite powder. The obtained carbon nanotube composite powder underwent a secondary dispersion test. Under mechanical stirring at a linear velocity of 3m / s for 30min, the secondary dispersion particle size D90 = 0.624μm, and the electrode resistivity when applied to the positive electrode of a lithium-ion battery was 18.4Ω·cm.
2. A carbon nanotube composite powder that does not require pre-dispersion, characterized in that, It was prepared using the preparation method described in claim 1.
3. The application of the carbon nanotube composite powder as described in claim 2 in lithium battery conductive agents, conductive plastics, transparent conductive films, supercapacitors, conductive inks, and high-strength superfibers.
Citation Information
Patent Citations
Aerogels based on carbon nanotubes
US20100092371A1